Which Fearful Toddlers Should We Worry About? Context, Fear Regulation, and Anxiety Risk - Buss, Kristin A. (2011)
The current study tests a model of risk for anxiety in fearful toddlers characterized by the regulation of the intensity of withdrawal behavior across a variety of contexts. Participants included 111, low-risk, 24-month-old toddlers followed longitudinally each year through the fall of their kindergarten year. The key hypothesis was that being fearful in situations that are relatively low in threat (i.e., are predictable, controllable, and in which children have many coping resources) is an early precursor to risk for anxiety development as measured by parent and teacher report of anxious behaviors in kindergarten. Results supported the prediction such that it is not how much fear is expressed, but when the fear is expressed and how it is expressed that is important for characterizing adaptive behavior. Implications are discussed for a model of risk that includes the regulation of fear, the role of eliciting context, social wariness, and the importance of examining developmental transitions, such as the start of formal schooling. These findings have implications for the way we identify fearful children who may be at risk for developing anxiety-related problems.